Correlation of Brothers' Earnings and Intergenerational Transmission - Bingley, Paul; Cappellari, Lorenzo (The Review of Economics and Statistics, 2019)
We model the correlations of brothers' earnings isolating the effect of fathers' earnings from additional residual influences shared between brothers. We separate the two effects by analysing sibling correlations and intergenerational correlations jointly within a unified framework. Our multi-person model of earnings dynamics distinguishes permanent from transitory shocks, allows for heterogeneous life cycle effects and nests previous models. Using data on the Danish population of father/first-son/second-son triplets, we corroborate the findings of studies that do not account for life cycle effects for those aged in their 30's, but find correlations twice as large at 25. The impact of intergenerational effects also varies over age, but is everywhere higher than found in previous studies ?by on average a factor of thirteen? and accounts for most of the sibling correlation. We provide evidence that lack of both life cycle effects and heterogeneous intergenerational transmission across families in previous studies explain the difference. When allowing for differential intergenerational transmission within families, we find mild evidence of stronger transmission to second sons.